Histopathologcial and clonal study of combined lobular and ductal carcinoma of the breast. (20th June 2013) - Tazaki, Eri; Shishido‐Hara, Yukiko; Mizutani, Natsuko; Nomura, Sachiyo; Isaka, Hirotsugu; Ito, Hiroki; Imi, Kentaro; Imoto, Shigeru; Kamma, Hiroshi
<x xml:space="preserve">Abstract</x> Lobular carcinoma in situ (LCIS) clinically constitutes a risk factor for the subsequent development of either invasive lobular carcinoma (ILC) or invasive ductal carcinoma (IDC). In order to approach the possibility of this common precursor of both ILC and IDC, we investigated combined lobular and ductal carcinomas. Thirty‐two cases of lobular carcinoma were picked up out of 773 cases of operated breast carcinomas. The histopathological detailed re‐examination using immunostain of E‐cadherin and β‐catenin revealed a rather high frequency of combined lobular carcinomas than previous reports. Clinicopathologically, combined lobular carcinomas were younger and smaller than pure lobular carcinomas, and the cytological atypia was relatively low. These results suggested that combined lobular carcinomas could be detected in the earlier stage of breast cancer. Furthermore, the lobular and ductal components of combined carcinomas coexisted in the neighborhood and were distributed contiguously. The immunohistochemical phenotypes of both components were accorded in most combined cases. A genetic analysis using methylation‐specific PCR on the HUMARA gene demonstrated that the same allele was inactivated in both lobular and ductal components in all detectable cases of combined carcinoma. Therefore, it is reasonable to assume that both lobular and ductal components of combined carcinomas are clonal and derived from the LCIS as the common precursor lesion, which may contradict the conventional concept that the lobular and ductal carcinomas arise from distinct differentiation pathways.